KEWENANGAN HAKIM TERHADAP ADANYA KETENTUAN PIDANA MINIMAL TERKAIT TINDAK PIDANA NARKOTIKA YANG DILAKUKAN OLEH ANGGOTA TNI (ANALISIS PUTUSAN NOMOR 108-K/PM.II-09/AD/IV/2015) - Rizky Meidiawan; Sugandi Ishak (Fakultas Hukum Universitas Tarumanagara, 2019)
One of the duties of the judge was to settle the case to sentence the perpetrators of the crime by saying that the defendant was acquitted or convicted based on at least 2 evidence and the judge based on the evidence was convinced that the error violated the article charged. The judge has the freedom to impose a sentence against the defendant who is not only fundamental to the provisions of the Law but also the judge can explore the values of law and justice in society. In the current practice, many judges have ruled below the minimum criminal provisions contained in an article as in the case of narcotics in this study. This cannot be blamed because the judge has the authority and freedom to make a decision, but this will certainly make legal certainty impossible. Legal problems in this research are how the authority of judges against the existence of a minimum punishment provision in narcotics crime and what constitutes the objective is stipulated by minimum punishment provisions. The research method taken is a normative juridical method, research data obtained through literature study and retrieval of decision files as a supplement. the results of the study show that judges may just make a decision under the minimum criminal provisions because the judge not only has to pay attention to legal certainty but also the purpose of other laws is to provide justice.